2013
DOI: 10.1007/s10753-013-9652-9
|View full text |Cite
|
Sign up to set email alerts
|

Host Modulation in Rheumatoid Arthritis Patients with TNF Blockers Significantly Decreases Biochemical Parameters in Periodontitis

Abstract: The aim of this study was to evaluate the effects of host modulation therapy on periodontal and biochemical parameters. Sixteen rheumatoid arthritis patients newly scheduled for anti-tumour necrosis factor (TNF) therapy were screened for 30 days. Periodontal parameters (clinical attachment level, probing pocket depth, bleeding on probing, plaque index and gingival index) as well as salivary and gingival crevicular fluid (GCF), interleukin (IL)-1β, IL-8 and monocyte chemoattractant protein-1 (MCP-1) levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 34 publications
5
43
0
2
Order By: Relevance
“…The results of periodontal assessments demonstrated a significant improvement of periodontal condition, as determined by GI, BOP, and PD, in patients with RA after ADA therapy. These results are consistent with the findings of other studies, 13‐17 suggesting a therapeutic efficacy of TNF inhibition on periodontal condition. The data also showed comparable levels of supragingival plaque and the same status of smoking and RA medication between baseline and reassessment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of periodontal assessments demonstrated a significant improvement of periodontal condition, as determined by GI, BOP, and PD, in patients with RA after ADA therapy. These results are consistent with the findings of other studies, 13‐17 suggesting a therapeutic efficacy of TNF inhibition on periodontal condition. The data also showed comparable levels of supragingival plaque and the same status of smoking and RA medication between baseline and reassessment.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, TNF inhibitors have been evaluated for their efficacy on periodontal condition in patients with RA 13‐17 . It has been shown that treatment with infliximab (IFX), a chimeric mouse/human anti‐TNF‐α monoclonal antibody, proved beneficial in suppressing periodontal disease in patients with RA 13,14,16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main etiologic factor of periodontitis is an interaction between periodontal pathogenic bacteria and host tissue response 24. Since discovering the importance of host immune response in the pathogenesis of periodontal diseases, scientists have investigated host modulation therapy, which alters host tissue response to reduce destructive factors and increase preventive mediators 5,6. Various host modulatory agents have been investigated, such as growth factors, tetracycline, antiosteoclastic drugs, antioxidants, enamel matrix proteins, anti-inflammatory drugs, and bone morphogenetic proteins 5,7–10.…”
Section: Introductionmentioning
confidence: 99%
“…A MCP-1 foi correlacionada com a gravidade da periodontite em diversos estudos (Longo et al, 2014;Gupta et al 2013;Üstün et al, 2013). Novamente após o no tratamento de um ano houve aumento nos níveis de MCP-1, o que não ocorreu no soro de indivíduos com PA no estudo de Shaddox et al (2013).…”
Section: Resultsunclassified